Characterization of nanostructured MgAl2O4 ceramics fabricated by spark plasma sintering. Issue 7 (15th May 2016) - Benaissa, S.; Hamidouche, M.; Kolli, M.; Bonnefont, G.; Fantozzi, G.
Abstract: The aim of this work is to investigate the effect of sintering temperature on the properties of nanostructured spinel (MgAl2 O4 )fabricated by Spark Plasma Sintering (SPS). The starting material was a pure spinel (MgAl2 O4 ) nanopowder. The sintering was carried out at T =1300 °C, 1350 °C and 1400 °C under a pressure of 73 MPa.The samples sintered at 1300 °C exhibit a finer microstructure (mean grain size is about 250 nm) than those sintered at 1350 °C and 1400 °C. The relative density is about 99.93% at 1300 °C, 99.63% at 1350 °C and 99.58% at 1400 °C due to the presence of some porosity in the fabricated samples. Samples sintered at 1300 °C have a good transmittance (70% at 550 nm and 78% at 1100 nm) compared to those sintered at 1350 °C and 1400 °C. Due to their high density and fine grain size, samples sintered at 1300 °C exhibit a Vickers micro-hardness Hv=18 GPa, elastic modulus E =228 GPa relatively more important than those measured on samples sintered at 1350 °C (Hv=15 GPa, E =172 GPa, ) and at 1400 °C (Hv=12 GPa, E =136 GPa). They present the reverse behavior for fracture toughness k IC (1.05 MPa √m for samples sintered at 1300 °C, 1.43 MPa √m for samples sintered at 1350 °C and 2.23 MPa √m for that sintered at 1400 °C). The tribological behavior of the MgAl2 O4 ceramic was equally studied: the friction coefficient µ is measured and increases with sintering temperature µ =0.06, µ =0.13, µ =0.18, respectively for sintering temperature of 1300 °C, 1350 °C and 1400 °C. The wear behavior is also examined and the mass loss increases with increasing sintering temperature.